The Statistical Fragility of Hamstring Versus Patellar Tendon Autografts for Anterior Cruciate Ligament Reconstruction: A Systematic Review of Comparative Studies. Issue 10 (August 2021) - Ehlers, Cooper B.; Curley, Andrew J.; Fackler, Nathan P.; Minhas, Arjun; Chang, Edward S.
Background: Evidence-based medicine utilizes data to inform clinical decision making, despite the ability of a small number of outcome reversals to change statistical significance. P values are common measurements of statistical significance that possess inherent flaws. The inclusion of the fragility index (FI) and fragility quotient (FQ) may provide a clearer conveyance of statistical strength. Purpose/Hypothesis: The purpose was to examine the statistical stability of studies comparing hamstring tendon and bone–patellar tendon–bone autografts in primary single-bundle anterior cruciate ligament reconstruction with independent tunnel drilling. We hypothesized that the findings of these studies are vulnerable to a small number of outcome event reversals, often fewer than the number of patients lost to follow-up. Study Design: Systematic review. Methods: Comparative studies and randomized controlled trials (RCTs) published in 10 leading orthopaedic journals between 2000 and 2020 were analyzed. Statistical significance was defined as a P value ≤.05. FI for each outcome was determined by the number of event reversals necessary to alter significance. FQ was calculated by dividing the FI by the respective sample size. Results: Of the 1803 studies screened, 643 met initial search criteria, with 18 comparative studies ultimately included for analysis, 8 of which were RCTs. A total of 114 outcomes were examined. Overall, the mean (interquartile range) FI and FQ were 3.77 (2-4) and 0.040 (0.016-0.055), respectively. The FI was less than the number of patients lost to follow-up for 76.3% of outcomes. Conclusion: Studies examining graft choice for anterior cruciate ligament reconstruction may not be as statistically stable as previously thought. Comparative studies and RCTs are at substantial risk for statistical fragility, with few event reversals required to alter significance. The reversal of <4 outcome events in a treatment group can alter the statistical significance of a given result; this is commonly fewer than the number of patients lost to follow-up. Future comparative study analyses might consider including FI and FQ with P values in their statistical analysis.